The role of glymphatic system in neurological diseases - literature review - Niekurzak, Karolina; Jędrak, Maciej; Kania, Krzysztof; Józefiak, Maciej; Sobkiewicz, Piotr; Kania, Joanna (Journal of Education, Health and Sport, 2023)
Abstract Introduction: The glymphatic system is the equivalent of the lymphatic system in the brain. This system is responsible for the exchange of metabolism waste products between the cerebrospinal fluid and the interstitial fluid. The glymphatic system functions mainly during sleep, and this is when the removal of interstitial metabolism waste products take place. A proper diet and physical activity are also needed for the glymphatic system to work effectively. Abnormal function of the glymphatic system can contribute to the development of diseases of the central nervous system, including neurodegenerative diseases and migraine. Aim of the study: The aim of our study is to review the latest knowledge linking the glymphatic system with the pathogenesis of selected neurological diseases and other lifestyle-related factors such as sleep, diet and physical activity. The study included Alzheimer’s disease, Parkinson’s disease, migraines and ischemic stroke. Materials and methods: We have reviewed the literature available in the pubmed database using keywords: “glymphatic system”; “aquaporin-4”; “Alzheimer’s disease”; “Parkinson’s disease”; “migraines”; “sleep” Conclusions: The studies discussed here show a clear correlation between the glymphatic system and neurological diseases. The glymphatic system may definitely be involved in the pathophysiology of neurological disorders. A thorough investigation of this issue will help uncover potentially new strategies for the prevention and treatment of neurological diseases. Key words: glymphatic system; aquaporin-4; Alzheimer’s disease; Parkinson’s disease; migraine; sleep